PERLINDUNGAN KESELAMATAN DAN KESEHATAN KERJA BAGI PEKERJA MEKANIK MOTOR DI PT. ALFA SCORPII KOTA PEKANBARU - Rizki Safitra Sulistio; Mexsasai Indra; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Occupational safety and health is a program created for workers or laborers and employers for events caused by work relationships in the work enviroment by identifying thing that have the potential to cause accident and diseases due to work relationshipand anticipatory action in the event of a work accident by providing guidance compensation and increasing recognition of socio economic human right and physical protection through noorms within the company.The purpose of this study was to determine how to establish occupational safety and health protection for mechanics at PT Alfa Scorpii Pekanbaru and find out efforts to overcome obstacles to the implementation of occupational safety and health protection for motorized mechanical workers. The type of research the author uses is empirical or sociological legal research by directly conducting research at the location under study in order to provide a complete and clear picture of the problem under study. The conclusions obtained from the research result are first, regarding occupational safety and health protection for motorbike mechanic workers at PT. Alfa Scorpii pekanbaru, it has not been implemented properly. Second, there are inhibiting factors in the application of occupational in the form of human factor, facilities, and infrastructure. The suggestions obtained are first, company should further increase supervision of workers who do not use personal protectve equipment. Second, companies and workers must know more about the impportance of oupational safety and health.Keywords: Legal Protection, Occupational Safety and Helth, Motor Mechanics.